METODE CUT AND FILL DAN SHRINKAGE FULL STOPING PADA PEMBANGUNAN TAMBANG BAWAH TANAH ( UNDERGROUND ACCESS LEVEL) - Gerie Munggaran (LPPM, 2016)
Purpose use of methods cut and fill and shrinkage full stoping, among which Know and exposure to exploitation and infrastructure mined underground by the method of cut and fill and methods of shrinkage, Adding insights about science and emerging technologies in the field of mining, As a means of comparison between the theory and practice of lectures with the application in the field. Cut and Fill is a mining method that is in use with a view to taking ore by means of a flat back or flat and after being discharged ore closed again by filling the bermaterial mix tailings with cement silo or west and proceed back to exploration, Shrinkage Full stoping is a methods used underground mines with the process system is where ore issued in this way can take over the mine from way by shifting the buffer board or from above through the ore cute.Keywords: Cut And Fill method and Skhrinkage Full stoping as the supporting infrastructure in underground mining.